The Effects of Azithromycin Modified Triple Antibiotic Paste in Resolving Periapical Inflammation - Tingting Meng; Zhengyang Wang; Haocong Li; Zhaoguang Ouyang; Chenxi Yang; Tengye Lian; Yao Zhang; Huixu Li; Pingping Bao; Dayong Liu (International Dental Journal, 2025)
Objective: This study aimed to assess the anti-inflammatory and antibacterial properties of traditional and modified triple antibiotic paste. The 16S rDNA was employed to analyse the root canal microbial community's characteristics pre- and post-treatment. Methods: Rabbits with periapical inflammation (AP) were treated with both pastes. Micro-CT was performed to compare the periapical lesion area, followed by HE staining. Inflammatory factors and microorganism were collected for analysis. T-tests and ANOVA were used to analyse the effects of the 2 pastes on tooth discoloration. Results: Compared with the control group, apical lesions and the expression of inflammatory cytokines was decreased, along with a reduction in bone destruction. Antibacterial experiments showed that the 2 antibiotics had similar effects on the common pathogens of AP. Compared with the TAP, mTAP does not cause discoloration of teeth. 16Sr DNA analysis revealed variations in periapical bacteria composition. The contents of common pathogens of AP in TAP and mTAP groups were lower than those in control group. Conclusions: Azithromycin has the potential to serve as an alternative to minocycline. The 16S rDNA data highlights the intricate nature of the root canal microbiome, promising deeper insights into the correlation between microbes and inflammation.